DNA technology in administration of justice - Adhikary, Jyotirmoy (New Delhi : LexisNexis Butterworths, 2007)
With reference to India
Includes index
Keywords: DNA fingerprinting -- Law and legislation; Evidence, Expert; Evidence, Criminal